Team-Based Learning & Point of Care Ultrasound (POCUS) to Augment a Preclinical Cardiovascular Physiology Course - Mark Danila; Cynthia Zheng; Ryan J. Salvatore; Rachel Cary; Sara Youssef; Grace Pinhal-Enfield; Catherine Chen (CINQUILL Medical Publishers Inc., 2024)
Introduction: There has been increasing interest in point of care ultrasound (POCUS) as a learning tool in preclinical medical anatomy and physiology courses. Few interventions have used team-based learning (TBL) to teach cardiac POCUS. This study investigates a novel TBL exercise designed to integrate cardiac anatomy, physiology, and cardiac POCUS education within a first-year cardiovascular (CV) course called Team-Based Learning - Ultrasound (TBL-US). Methods: The TBL-US exercise consisted of four phases: preparation, individual and team readiness assurance, image acquisition and application, and knowledge assessment. Six second-year students were trained to facilitate the session under physician supervision. Pre- and post-session knowledge assessments were administered to determine knowledge acquisition. Pre- and post-session surveys were administered to assess attitudes, beliefs, and confidence surrounding cardiac POCUS. Final exam scores were compared between participants and non-participants of TBL-US and stratified into high- and low-performing subgroups to account for pre-TBL baseline differences in ability between the groups. Results: A total of 54 first-year medical students completed TBL-US. Students showed significant improvement on the post-knowledge assessment compared to the pre-knowledge assessment (70.5% vs. 54.9% [p< 0.001]) and scored significantly higher on the final CV exam compared to non-participants (low-performing group: 85.92% vs. 81.02% [p=0.039], high-performing group: 89.22% vs. 85.95% [p=0.038]). Between 43.3-72.7% of students reported that TBL-US increased their understanding of CV anatomy, physiology, and cardiac POCUS. Discussion: Students found TBL-US to be a valuable teaching modality and improved student knowledge of CV anatomy, physiology, and cardiac POCUS. TBL-US effectively augments the learning of cardiac anatomy and physiology during the preclinical undergraduate medical curriculum.